The Dynamics of the Price of Raw Materials and Industrial Strategies in African Producer Countries: What are the Challenges? - Yves Jégourel; Philippe Chalmin (Revue Internationale de Politique de Développement)
Obviously, the fall in the price of raw materials observed since 2014 is not good news for producer countries, especially those in Africa. While some people are already invoking the ‘natural resource curse’ to explain the economic and political fragility that can result from excessive variability in the price of commodities, it should be borne in mind that the trajectory of these countries is in no way predetermined, but depends largely on the macroeconomic context in which they operate, as well as on the quality of the policies implemented to counter the negative effects of this instability. In a difficult context which will probably persist, despite the rebound observed in 2016, producer countries will need to cope with many challenges to maintain a positive trajectory tending towards greater economic diversification.